TEACHERS' PERSPECTIVES ON OBSTACLES AND SOLUTION STRATEGIES IN MATHEMATICS TEACHING IN INCLUSIVE ELEMENTARY SCHOOL CLASSES - Susilo Hadi; Reza Rachmadtullah; Dudu Suhandi Saputra; Budi Febriyanto (Universitas Majalengka, 2023)
This study aims to identify the challenges faced by teachers in teaching mathematics in inclusive elementary school classrooms and the solution strategies implemented to overcome these challenges. Teaching mathematics in inclusive classrooms involves students with diverse abilities, including students with special needs, which complicates the learning process. The research method used was descriptive qualitative, with data collected through in-depth interviews and observations of several teachers teaching in inclusive elementary school classrooms. The results indicate that the main challenges faced by teachers include differences in academic ability levels among students, limited resources, complex classroom management, difficulties in managing the behavior of students with special needs, and a lack of adequate training and support for teachers. Teachers face challenges in adapting teaching materials and teaching methods to meet the diverse needs of students, which impacts learning effectiveness. Furthermore, limited access to appropriate tools and technology is also a hindering factor. To overcome these challenges, teachers implement various solution strategies, such as using more flexible teaching methods and collaborating with support staff and specialists to provide more attention to students with special needs.